From the Banks of the Orkhon to the Banks of the Neva: the History of Mining and Transit of Mongolian Gold to the Russian Empire at the beginning of the 20th century. - Aldar A. Shirapov; Anna M. Plekhanova (Монголоведение)
Introduction. This scientific study examines the history of the organization of gold mining in a Russian company — the Joint Stock Company of Mining of the Tushetukhanovsky and Tsetsenkhanovsky aimags in Mongolia (“Mongolor”). The purpose of the research is to study the mechanism of delivery of Mongolian gold to the Russian territory; identify and evaluate the role of the Russo-Chinese Bank and the Kyakhtinsky District Treasury in this process. Materials and methods. The study is based on the analysis of data from regulatory documents contained in the Complete Collection of Laws of the Russian Empire and previously unpublished cases from the funds of the State Archive of the Republic of Buryatia and the Russian State Historical Archive. In his research, the author used a number of general scientific and special historical methods. The main method used is historical-genetic, the use of which helped to identify the reasons according to which the Mongolor joint-stock company was created, as well as to reconstruct the mechanism of both gold production by this company and its further transit to Russia. The author's application of the theory of modernization made it possible to consider the financial policy pursued by the authorities of the Russian Empire as the main tool in the modernization of the state. Results. The flourishing of the economy of the Russian Empire in the 1890s was largely possible due to the well-thought-out financial policy pursued by the country's authorities. Thanks to the successfully implemented monetary reform, the author of which was Minister of Finance S.Yu. Witte, the Russian ruble has become one of the most stable world currencies. The strengthening of the ruble exchange rate and its free conversion provided the country with an influx of foreign investment, which contributed to the constant growth of its economy. In order to maintain the growth rate of the commercial and industrial sector of the empire, the power circles of the Russian Empire were constantly looking for opportunities to increase the gold reserves of the state. At the beginning of the 20th century, one of the sources of gold for Russia were mines in the northern regions of Mongolia. A company created under the control of the Russian government, the Joint-Stock Company of Mining of the Tushetukhanovsky and Tsetsenkhanovsky aimags in Mongolia (“Mongolor”), was able to quickly establish the extraction of the precious metal. The resulting gold was sent to Russia with the help of the Russo-Chinese Bank and the Kyakhtinsky District Treasury. Through joint efforts, employees of these financial organizations were able to establish a highly efficient mechanism for transporting Mongolian gold. Conclusions. The Joint-Stock Company for the Mining of the Tushetukhanovsky and Tsetsenkhanovsky aimags in Mongolia (“Mongolor”), created with the support of the Russo-Chinese Bank and foreign capital, is an example of a successful business project that not only helped to significantly replenish the gold reserves of the Russian Empire but contributed to the strengthening of Russian influence in Mongolia